Valuation of ex-mining lands : the preferred methods / Nur Syahidah Shamsul Hasni and Noryanto Asroun Mohamad Asroun - Shamsul Hasni, Nur Syahidah; Mohamad Asroun, Noryanto Asroun (2018)
Redevelopment of brownfield sites in Malaysia has been increasing over the years due to scarcity of land. The redevelopment of land is done to lands that no longer have their initial function such as ex-tin mining lands. Due to increase in redevelopment of ex-tin mining lands, government valuers carry out many valuations for land alienation purpose. However, discussion on valuation of ex-tin mining lands in Malaysia is very limited. Therefore, the objectives of this paper are to identify the factors that need to be taken into account in the valuation of ex-tin mining lands; and to determine the preferred methods of valuation for ex-tin mining lands. This paper adopts a qualitative approach by interviewing the experts and analysing the data using Atlas.ti to achieve the objectives.